Factors Affecting the Performance of Educational Projects (Journal of Engineering, 2025)
Governments allocate large sums of money annually to establish educational projects such as schools, given the importance of the education sector in the development of society. However, most of these projects suffer from poor performance. This research aims to identify the most important factors that affect educational projects in order to improve their performance and make them a suitable environment for education. Through a review of previous literature, a questionnaire was prepared to obtain the required data, which included five main categories covering a range of factors that affect performance. It was distributed to a number of specialized engineers, with different academic degrees and job titles, working in the educational buildings sector. After obtaining the results from 49 respondents and processing them using SPSS-BIM version 23, and calculating the relative importance index, it was found that the factors falling under the categories of “project manager” and “planning” were among the most influential factors in project performance. The most influential factors in each category were as follows: Project manager: Inefficiency, poor management, slow decision-making; senior management: Funding versus work completed, management support, hostile environment; planning: Weak and unstable, non-compliance with contract terms, changes in design and quantities; site: availability of skilled labour, construction methods, coordination between parties, machine setup, construction errors, material-related factors, and human resource experience and training; Monitoring and evaluation: issues related to monitoring and evaluation budgets and planning for monitoring and evaluation. Based on the results, a framework was developed to improve the performance of educational projects.